Development and Validation of the Pre-service Teacher Competency Scale in an Online Learning Environment Using the Scenario Method - Jiwon Baek; Jiwoo Kim; Hyeonseong Lee; Youn-Jeng Choi (SAGE Open, 2025)
The rapid shift to online learning during the COVID-19 pandemic highlighted the need to equip future educators with essential skills for an online learning environment. This study aims to address this gap by developing and validating a scale to measure pre-service teacher competency in an online learning context using the scenario method. After a comprehensive literature review, seven competencies of pre-service teachers in an online learning environment were constructed: design/planning competency, social competency, instructive competency, technological competency, management competency, positive teacher attitude competency, and learning competency. The Pre-service Teacher Competency in Online Learning Environments Scale was developed with 11 scenarios and 34 items and refined based on feedback from focus group interviews with six pre-service teachers and five in-service teachers to ensure face and content validity. The scale was then validated through confirmatory analyses and reliability analyses with 579 pre-service teachers, demonstrating good construct validity and reliability. This study contributes to teacher education by providing a validated tool that can help evaluate and enhance pre-service teacher preparation programs for online and hybrid learning environments.